FROM TRADITIONAL REPORTING TO DYNAMIC VLOGS: THE CHANGING FACE OF ON-CAMERA JOURNALISM - Zhang, Xuan (Current Journal of Humanities, Arts and Social Sciences (CJHASS), 2024)
The role of on-camera journalists in news reporting has evolved significantly since CCTV’s "The News Investigation" program introduced the tandem process of on-camera reporters in 1996. While their identity may have remained consistent, their functions have gradually shifted towards that of hosts or crosstalk performers. This transformation is evident in the diverse forms of reporting employed by on-camera journalists today, ranging from traditional live reporting to live streaming connections and dynamic vlogs. Moreover, their scope of application has expanded beyond traditional TV news to include new communication media such as short videos and webcasts, reflecting the trend of diversified communication channels